24-H-AMBULATORY BLOOD PRESSURE IN SUB-SAHARAN AFRICA: PREVALENCE OF WHITE COAT OR MASKED HYPERTENSION AND DISRUPTED DIPPING PATTERNS IN HIV+ PATIENTS ON ANTIRETROVIRAL THERAPY. (April 2021) - Kasper, Philipp; Phiri, Sam; Chaweza, Tom; Tweya, Hannock; Mwagomba, Beatrice; Muula, Adam; Nhlema, Angellina; Chiwoko, Jane; Neuhann, Florian; Steffen, Hans-Michael
Abstract : Objective: Background: Cardiovascular disease and especially hypertension are a growing problem among people living with HIV (PLHIV) on antiretroviral therapy (ART) in sub-Saharan Africa. As robust data on hypertension phenotypes associated with distinct cardiovascular risks among PLHIV are limited, we aimed to assess the frequency of white-coat (WCH) or masked (MH) hypertension and blood pressure dipping-patterns in a group of Malawian PLHIV. Methods: As part of the prospective Lighthouse-Tenofovir-Cohort-Study, we analyzed clinical, laboratory and 24-h-ambulatory blood pressure monitoring (ABPM) data of PLHIV from urban Lilongwe with known treated or untreated hypertension or raised office blood pressure (OBP) during routine study-visits (hypertension unknown and untreated). Design and method: 118 PLHIV were included and data of 117 participants could be analyzed. 24-h ABPM-normotension was found in 14/37 PLHIV with known treated hypertension (37.8%), 19/24 with known untreated hypertension (79.2%) and 40/56 with raised OBP (unknown/untreated hypertension; 71.4%). Using the strict definition of controlled hypertension or true normotension, i.e. normal OBP plus normal mean BP for all periods of ABPM the corresponding rates were 10.8%, 41.7%, and 39.3%. WCH with normal BP during all periods of 24-h-ABPM was identified in 12/64 OBP-hypertensive PLHIV (18.8%), primarily in patients with grade 1 hypertension (11/41 patients; 26.8%). MH was found in 17/53 PLHIV with OBP-normotension (32.1%), predominantly in patients with high normal BP (11/20 patients; 55%). The estimated glomerular filtration rate was significantly lower in MH compared to strictly defined normotensive PLHIV (92.0 ± 20.4 vs. 104.8 ± 15.7 ml/min/m 2, p = 0.031). 64.1% of PLHIV (59.5% with 24-h hypertension and 66.7% with 24-h normotension) had abnormal systolic dipping. Conclusion: The high prevalence of WCH and MH with early signs of renal end-organ damage and an abnormal dipping in approximately 2/3 of PLHIV warrants further confirmation as these factors may contribute to the increased cardiovascular risk of PLHIV in resource-limited settings like Malawi. Figure. No caption available.